Changes in Gait Characteristics of Stroke Patients with Foot Drop after the Combination Treatment of Foot Drop Stimulator and Moving Treadmill Training - Chen Peishun; Zhou Haiwang; Li Taotao; Guan Hongli; Min Yu; Zhang Wanrong (Neural Plasticity)
Objective. To study the changes in gait characteristics of stroke patients with foot drop after the combination treatment of foot drop stimulator and moving treadmill training and thus provide a basis for the improvement in a foot drop gait after stroke. Methods. Sixty patients with hemiplegia and foot drop caused by stroke were randomly divided into two groups of 30: the test group and the control group. Both groups received basic rehabilitation training. On this basis, the test group received the combination treatment of foot drop stimulator and moving treadmill training. The control group received foot drop stimulator training. Both groups received consecutive treatment for 3 weeks, five times a week, and every single time lasted for 30 minutes. Before and after the treatment, a gait watch three-dimensional gait analysis system was used to measure and record the maximum angles of flexion of the affected side’s hip, knee, and ankle; the pace; the step length asymmetry; the iEMG of the tibialis anterior muscle; the functional ambulation category; and Ashworth’s modified spasticity classification of the gastrocnemius. Results. After treatment, in the two groups, the maximum angles of flexion of the affected side’s hip, knee, and ankle improved, the pace increased, the step length asymmetry decreased, the iEMG of the tibialis anterior muscle increased, the functional ambulation category improved, and Ashworth’s modified spasticity classification of the gastrocnemius decreased, but the above changes in the test group were better than those in the control group. The difference is statistically significant (p<0.05). Conclusions. The combination treatment of the foot drop stimulator and moving treadmill can significantly improve stroke patients’ foot gait and promote the normalization of hip flexion, knee flexion, and ankle flexion. It can increase the pace, significantly reduce the step length asymmetry, reduce the muscle tone of the gastrocnemius, and improve walking function.